HEART RATE VARIABILITY IN HEMODIALYSIS PATIENTS - Loboda, O. M.; Dudar, I. O.; Gonchar, Y. I. (Ukrainian Journal of Nephrology and Dialysis, 2017)
There are a small number of works that have studied heart rhythm variability parameters in patients treated with hemodialysis. Aim. To investigate the peculiarities of heart rhythm variability parameters in patients treated with hemodialysis. Methods. The observational controlled study included 55 patients treated with hemodialysis, aged 24 to 75 years, including 29 men and 26 women. The control group consisted of 20 healthy individuals of comparable age and sex. Heart rhythm variability parameters were investigated in all patients. Results. In the study of heart rhythm variability in patients treated with hemodialysis comparatively with the control group time parameters and most of frequency indexes were decreased. Conclusions. Our study found the diminishment of the total power of neurohumoral regulation in patients treated hemodialysis, as evidenced by the low values SDNN, rNN50, CV.